Advanced head and neck surgery training during the COVID‐19 pandemic. Issue 7 (8th May 2020) - Givi, Babak; Moore, Michael G.; Bewley, Arnaud F.; Coffey, Charles S.; Cohen, Marc A.; Hessel, Amy C.; Jalisi, Scharukh; Kang, Steven; Newman, Jason G.; Puscas, Liana; Shindo, Maisie; Shuman, Andrew; et al.
Abstract: Background: The COVID‐19 pandemic has significantly impacted medical training. Here we assess its effect on head and neck surgical education. Methods: Surveys were sent to current accredited program directors and trainees to assess the impact of COVID‐19 on the fellow's experience and employment search. Current fellows' operative logs were compared with those of the 2018 to 2019 graduates. Results: Despite reduction in operative volume, 82% of current American Head and Neck Society fellows have reached the number of major surgical operations to support certification. When surveyed, 86% of program directors deemed their fellow ready to enter practice. The majority of fellows felt prepared to practice ablative (96%), and microvascular surgery (73%), and 57% have secured employment to follow graduation. Five (10%) had a pending job position put on hold due to the pandemic. Conclusions: Despite the impact of the COVID‐19 pandemic, current accredited trainees remain well‐positioned to obtain proficiency and enter the work‐force.